Proliferative effects of 'fibre' on the intestinal epithelium: relationship to gastrin, enteroglucagon and PYY. (1987) - Goodlad, R A; Lenton, W; Ghatei, M A; Adrian, T E; Bloom, S R; Wright, N A
Abstract : Refeeding starved rats with a fibre free 'elemental' diet increased crypt cell production rate (CCPR) in the proximal small intestine but not in the distal regions of the gut. Little effect on CCPR was seen when inert bulk (kaolin) was added to the 'elemental' diet. Addition of a poorly fermentable dietary 'fibre' (purified wood cellulose) had little effect on intestinal epithelial cell proliferation except in the distal colon where it significantly increased CCPR. A more readily fermentable 'fibre' (purified wheat bran) caused a large proliferative response in the proximal, mid and distal colon and in the distal small intestine. A gel forming 'fibre' also stimulated proliferation in the distal colon. There was no significant correlation between CCPR and plasma gastrin concentrations, but plasma enteroglucagon concentrations were significantly correlated with CCPR in almost all the sites studied. Plasma PYY concentrations also showed some correlation with CCPR, especially in the colon. Thus, whilst inert bulk cannot stimulate colonic epithelial cell proliferation, fermentable 'fibre' is capable of stimulating proliferation in the colon, and especially in the distal colon: it can also stimulate proliferation in the distal small intestine and it is likely that plasma enteroglucagon may have a role to play in this process.